Treating Alzheimer's disease by targeting iron. (11th February 2019) - Nikseresht, Sara; Bush, Ashley I.; Ayton, Scott
Abstract : No disease modifying drugs have been approved for Alzheimer's disease despite recent major investments by industry and governments throughout the world. The burden of Alzheimer's disease is becoming increasingly unsustainable, and given the last decade of clinical trial failures, a renewed understanding of the disease mechanism is called for, and trialling of new therapeutic approaches to slow disease progression is warranted. Here, we review the evidence and rational for targeting brain iron in Alzheimer's disease. Although iron elevation in Alzheimer's disease was reported in the 1950s, renewed interest has been stimulated by the advancement of fluid and imaging biomarkers of brain iron that predict disease progression, and the recent discovery of the iron‐dependent cell death pathway termed ferroptosis. We review these emerging clinical and biochemical findings and propose how this pathway may be targeted therapeutically to slow Alzheimer's disease progression. Linked Articles: This article is part of a themed section on Therapeutics for Dementia and Alzheimer's Disease: New Directions for Precision Medicine. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.18/issuetoc